Analysis of the Effects of Cryopreservation on Rat Hepatocytes Using SELDI-TOF Mass Spectrometry - Claire Terry; Matthew Bailey; Ragai R. Mitry; Sharon C. Lehec; Anil Dhawan; Robin D. Hughes (Cell Transplantation, 2006)
Successful cryopreservation of hepatocytes is essential to the future of hepatocyte transplantation as a treatment for liver disease, and also for the improved in vitro use of hepatocytes for research. However, hepatocyte function is adversely affected by even the best cryopreservation protocols. To investigate possible mechanisms for these changes, total cell lysates were prepared from fresh and cryopreserved rat hepatocytes and the proteome profiles compared using SELDI-TOF-MS ProteinChip? technology. In addition, in vitro functional assays (viability, attachment efficiency, and lactate dehydrogenase leakage) were performed on the corresponding fresh and cryopreserved hepatocytes. Sixty-one peptides were identified as being significantly changed after cryopreservation. Thirty-seven peaks were significantly increased and 24 were significantly decreased after cryopreservation. The peak intensity of a number of these peptides was found to correlate with the in vitro function of the hepatocytes. Seven peptides correlated with in vitro function after cryopreservation and 10 peptides correlated with both fresh and cryopreserved function. The peptides significantly decreased after cryopreservation could include cytosolic enzymes or cofactors, which leaked out of the cells due to cryopreservation-induced membrane damage. The peptides significantly increased after cryopreservation could be retained products of cleavage of larger intracellular polypeptides and proteins or the result of aggregation of peptides caused by physical changes in the cell due to the cryopreservation process. Proteome profiling using SELDI-TOF-MS could be a useful tool to assess the effects of isolation and cryopreservation of hepatocytes, particularly if the findings are extended to human hepatocytes.